Day 1 Mon, November 09, 2020 2020
DOI: 10.2118/203069-ms
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sand Consolidation as an Effective Alternative to Conventional Sand Control Methods in Ecuador

Abstract: This paper shows the results from chemical sand consolidation treatments used in the M1 sandstone as the main sand control method. For a successful implementation of this technique a workflow that combines field data, temperature modeling, laboratory analysis, petrophysics and geomechanics has been developed. Production results reports zero to near zero sand production with almost no impact on well productivity. Pre job design steps used to secure a consolidated reservoir after the treatment are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Compared to conventional dense resins, the pores of the porous polyurethane provide seepage channels that limit permeability reduction . Many field applications have shown that resin injection for sand production control can effectively improve reservoir mechanical properties and reduce sand production (El-monier et al, 2013;Shang et al, 2019;Izurieta et al, 2020;Mahardhini et al, 2021;Zaitoun et al, 2022;Miri et al, 2023;Peerakham et al, 2023;Stephen Babagbemi et al, 2023).…”
Section: Resin Injection Methodsmentioning
confidence: 99%
“…Compared to conventional dense resins, the pores of the porous polyurethane provide seepage channels that limit permeability reduction . Many field applications have shown that resin injection for sand production control can effectively improve reservoir mechanical properties and reduce sand production (El-monier et al, 2013;Shang et al, 2019;Izurieta et al, 2020;Mahardhini et al, 2021;Zaitoun et al, 2022;Miri et al, 2023;Peerakham et al, 2023;Stephen Babagbemi et al, 2023).…”
Section: Resin Injection Methodsmentioning
confidence: 99%
“…On the other hand, production factors are closely related to mining methods, production pressure differences, mining speeds, and wellbore design. Unreasonable mining methods, excessive production pressure differences, or excessively fast mining speeds can all increase the scouring force of fluids on the particles of the reservoir framework, leading to sand production (Izurieta A et al, 2020;Ayazi P et al, 2021;Hasmin et al, 2022a;Mandhari S et al, 2022).…”
Section: Causes Analysis Of Sand Production In Oil Wellsmentioning
confidence: 99%
“…In its application, there are two common forms: sand control pipe technology and improved sand control pipe technology -gravel packing technology for pipe strings. The former mainly establishes a sand barrier within the wellbore using sand control pipes, while the latter primarily relies on the compaction of gravel between the sand control pipe and the casing to block the flow of ceramsite, and also uses sand control pipes within the wellbore for sand prevention (Hurt R S and Germanovich L N, 2012;Dong, C., et al, 2016;Safaei, A., et al, 2023b).…”
Section: Mechanical Sand Controlmentioning
confidence: 99%
“…This method also causes a sharp decline in permeability due to filling the porous media around the wellhead. In earlier methods, known as underground methods, the injection process occurs in three stages . First, some soluble monomers are injected into the formation to fill the space between the sands.…”
Section: Chemical Treatment For Sand Controlmentioning
confidence: 99%
“…In earlier methods, known as underground methods, the injection process occurs in three stages. 155 First, some soluble monomers are injected into the formation to fill the space between the sands. In the second stage, an inert fluid is injected to move the monomers through the pores into the formation and prevent the blockage of these porous media.…”
Section: Application Of Chemicals For Sand Consolidationmentioning
confidence: 99%